Making A Web-Based Visual Novel Game To Introduce The Library Of UNIKA Soegijapranata - Alvin L.K, Alfonsus; Harnadi, Bernardus; P, FX Hendra (Soegijapranata Catholic University, 2024)
As technology develops, its impact can be felt in human daily life. One of the aspects affected by the development of technology is the library. The library must be able to show that the library can also adapt as technology evolves. Of course this also applies to the library of Unika Soegijapranata, the game